2022
DOI: 10.1007/s00520-022-07490-9
|View full text |Cite
|
Sign up to set email alerts
|

What do bereaved relatives of cancer patients dying in hospital want to tell us? Analysis of free-text comments from the International Care of the Dying Evaluation (i-CODE) survey: a mixed methods approach

Abstract: Purpose We conducted an international survey of bereaved relatives of cancer patients dying in hospitals in seven countries, with the aim to assess and improve the quality of care. The survey used the i-CODE (International Care of the Dying Evaluation) questionnaire. Here, we report findings from the free-text comments submitted with the questionnaires. We explored for topic areas which would potentially be important for improving the quality of care. Further, we examined who reported free-text… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“… Winters (2022) also suggested that psychological changes lead to a disruption of one’s physical and mental balance and predisposition to autoimmune diseases, which can have adverse effects on cancer treatment, recovery, and social stability ( Grossman et al, 2018 ; Courtney et al, 2020 ). Furthermore, related studies have shown that the organic combination of proximal and intimate relationship defenses have somewhat similar effects to that of palliative care for patients with advanced cancer ( Snaman et al, 2020 ; Gerlach et al, 2022 ).…”
Section: Introductionmentioning
confidence: 98%
“… Winters (2022) also suggested that psychological changes lead to a disruption of one’s physical and mental balance and predisposition to autoimmune diseases, which can have adverse effects on cancer treatment, recovery, and social stability ( Grossman et al, 2018 ; Courtney et al, 2020 ). Furthermore, related studies have shown that the organic combination of proximal and intimate relationship defenses have somewhat similar effects to that of palliative care for patients with advanced cancer ( Snaman et al, 2020 ; Gerlach et al, 2022 ).…”
Section: Introductionmentioning
confidence: 98%